PHYSIOLOGICAL DISORDERS AFFECTING DENDROMETRIC PARAMETERS AND EUCALYPTUS WOOD QUALITY FOR PULPING WOOD - Ana Paula Câmara (CERNE, 2018)
The productive sustainability of eucalyptus planting is threatened when both diseases and disorders of growth occur. These interferences can have abiotic origin as environmental conditions can negatively affect the wood quality. This study has the goal of evaluating influence of different levels of physiological disorders in dendrometric variables and wood quality from seven-year-old Eucalyptus grandis x Eucalyptus urophylla hybrids intended for wood pulping production. The trees from commercial plantations in State of Maranhão, Brazil were separated into three levels of physiological disorders by means of morphologic changes. Then, they were evaluated according to dendrometric variables, anatomical characteristics, chemical properties, density of wood, and kraft pulp process. The physiological disorder levels significantly influenced all evaluated properties. Moreover, the wood from trees with higher severity of symptoms resulted in higher average values of dendrometric variables, basic density, and fibers dimensions. In addition, apparent density exhibited a different standard in the pith region with increase on radial wood profile. Trees with the least severe disorders exhibited changes in dendrometric and anatomical variables, mainly in wood volume and fibers dimensions, respectively.